PEMEROLEHAN BAHASA INDONESIA PADA ANAK BERKEBUTUHAN KHUSUS (STUDI KASUS AHMAD ZAKIR MA ARIF) - Yani, Ade Irma; Patriantoro, Patriantoro; Jupitasari, Mellisa (Universitas Tanjungpura, 2024)
This research aims to find out about Indonesian language acquisition in children with special needs (Down Syndrome) case study of Ahmad Zakir Ma Arif, psycholinguistic studies. This research uses descriptive method with qualitative research form. The data source of this research is obtained directly from the subject of a child with Down syndrome, the research data is Indonesian sentence patterns in accordance with the formulation of the selected problem. The data collection techniques used in this research are observation, documentation, and interviews. The data collection tools used are recording devices, stationery. After that, the results of the analysis show that declarative sentences (news) are 20 sentences, imperative sentences (orders) are 10 sentences. Interrogative sentences (question) as many as 3 sentences. From the results of the data analysis that has been carried out, the most dominant sentence obtained by children with Down syndrome is a declarative sentence, actually children with Down syndrome understand what other people say, but they only have difficulty pronouncing words to answer what other people say, therefore parents must early train and conduct therapy for children with Down syndrome.